A Study of the Strategic Alliances’ Impact on the Relationship among Organizational Learning, Innovation, and Firm Financial Performance - Bahman Hajipour; Morteza Kord (مطالعات مدیریت بهبود و تحول, 2011)
Pursuit of superior financial performance is one of the most important  issues for firms and management researchers. This study examines the relationship among organizational learning, innovation and financial performance, and that whether this relationship improves in the context of strategic alliances. We tested our model on a sample of 105 partnering firms, applying structural equation modeling based onPartial Least Squares (PLS) methodology. Results suggest a significant and positive relationship among organizational learning, innovation and financial performance. Also, it is manifested that this relationships becomes stronger in cases of firms partnering together.